TURNING THE TIDE: REVISITING AFRICAN MARITIME SECURITY - Vrey, Francois (Scientia Militaria - South African Journal of Military Studies, 2013)
Maritime security appears to be assuming an increasingly more prominent place on the African security agenda. Although the growing scholarly debate and international responses seem to attend to more than piracy, the latter unfortunately skews perceptions about Africa’s maritime landscape. The piracy focus suggests a limited problem-solving approach, but Africa’s offshore domain calls for a more critical stance that entails more than anti-piracy. Perceptions and realities of maritime terrorism, piracy, illegal oil bunkering, criminality and unsettled maritime boundaries increasingly complicate traditional African threats and vulnerabilities on land. The growing range of threats requires a framework to explain events taking shape off West and East Africa in particular better. In this regard, the constituent elements of good order at sea house a more critical line to view security off Africa through safe access to resources (food and minerals), safe sea routes, as well as dominium and jurisdiction. Opposition to threats off the African coast tends to privilege naval responses, but closer scrutiny reflects that responses are found to also display a profile of cooperation between numerous actors and agencies that securitise maritime threats beyond piracy. The resultant cooperation reveals landward and offshore initiatives that promote maritime security, rather than merely fighting piracy.